The turning point in an unwanted teenage pregnancy: a psycho-emotional perspective - Mohamad Nor, Azmawaty; Sharatol Ahmad Shah, Shanina; P Balasingam, Usharani; Zainudin, Zaida Nor (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Malaysia is a multiethnic country that allows freedom of religion with Islam being the most professed religion. Under the Islamic teachings, premarital sex is forbidden. Nonetheless, at present, there is an increasing number of teenage pregnancies among the Malay Muslims as a consequence of premarital sex. The objective was to obtain a detailed understanding of how pregnant teenagers make sense of their experience with unwanted pregnancy from a psycho-emotional perspective. Methods: Purposive sampling through the application of Interpretative Phenomenological Analysis (IPA) was employed. Face to face interviews were conducted with 10 participants that were 17 years old. Results: Three themes emerged from the present research (a) transformation of self, (b) transition to motherhood and; (c) spiritual strengthening. Conclusion: All participants experienced turning points in their lives in which they made sense of their experience resulting in positive changes.